PENEGAKAN HUKUM TINDAK PIDANA PERIKANAN TERHADAP ILEGAL FISHING MELALUI MEKANISME PENENGGELAMAN KAPAL - Indra Rusdian Lego (Jurnal Akrab Juara, 2018)
Law enforcement of fisheries crimes through the mechanism of drowning foreign vessels that commit fisheries crime has not run optimally because there is no public participation involved in supporting the eradication of IUU Fishing and there are still differences in views on the sinking of ships and the burning of foreign ships between PSDKP, Polri and TNI AL related to sufficient preliminary evidence. This is not in line with Lawrence M. Friedman's theory which emphasizes that law enforcement depends on the substance of the law, legal structure / legal institutions and legal culture. The legal consequences of law enforcement in the field of fisheries through the mechanism of sinking foreign vessels that commit fisheries crime in Indonesian waters if linked to UNCLOS 1982, so far there have been no negative consequences experienced by Indonesia due to these strict actions, this is because internationally IUU fishing has been become a common enemy and the decisive action of the sinking of the vessel is the implementation of the rule of law of the Republic of Indonesia. Keywords: Law Enforcement, Foreign Vessel Sinking, Crime Fisheries